Comparing stacking ensemble techniques to improve musculoskeletal fracture image classification - Kandel, Ibrahem (2021)
Kandel, I., Castelli, M., & Popovič, A. (2021). Comparing stacking ensemble techniques to improve musculoskeletal fracture image classification. Journal of Imaging, 7(6), 1-24. [100]. https://doi.org/10.3390/JIMAGING7060100